Study of M. M. Prishvin's creativity in the framework of extracurricular activities - Ol'khovskaia I. I., Kolbina V. A. (Pedagogical and sociological aspects of education, 2019)
The article presents the development of extracurricular activities on the fairy tale-the story of M. M. Prishvin "Pantry of the sun" in the framework of extracurricular activities in literature. The event is designed for students of 5-6 classes and takes into account the features of the system-activity approach in teaching literature.
Keywords: внеурочная деятельность; русская литература; extracurricular activities; Пришвин; Кладовая солнца; методика обучения литературе; Russian literature; Prishvin; Pantry of the sun; methods of teaching literature